Cotinus coggygria Scop. induces cell cycle arrest, apoptosis, genotoxic effects, thermodynamic and epigenetic events in MCF7 breast cancer cells. - Gospodinova Zlatina I.; Zupkó István; Bózsity Noémi; Manova Vasilissa I.; Georgieva Mariyana S.; Todinova Svetla J.; Taneva Stefka Germanova; Krasteva Maria Emileva; Ocsovszki Imre (2021)
Current plant-derived anticancer therapeutics aim to reach higher effectiveness, to potentiate chemosensitivity and minimize the toxic side effects compared to conventional chemotherapy. Cotinus coggygria Scop. is a herb with high pharmacological potential, widely applied in traditional phytotherapy. Our previous study revealed that leaf aqueous ethanolic extract from C. coggygria exerts in vitro anticancer activity on human breast, ovarian and cervical cancer cell lines. The objective of the present research was to investigate possible molecular mechanisms and targets of the antitumor activity of the extract in breast cancer MCF7 cells through analysis of cell cycle and apoptosis, clonogenic ability assessment, evaluation of the extract genotoxic capacity, characterization of cells thermodynamic properties, and analysis on the expression of genes involved in cellular epigenetic processes. The obtained results indicated that in MCF7 cells C. coggygria extract causes S phase cell cycle arrest and triggers apoptosis, reduces colony formation, induces DNA damage, affects cellular thermodynamic parameters, and tends to inhibit the relative expression of DNMT1, DNMT3a, MBD3, and p300. Further studies on the targeted molecules and the extract anti-breast cancer potential on animal experimental model system, need to be performed in the future.